2024
DOI: 10.1071/wf23143
|View full text |Cite
|
Sign up to set email alerts
|

Live trial performance of the Australian Fire Danger Rating System – Research Prototype†

S. Grootemaat,
S. Matthews,
B. J. Kenny
et al.

Abstract: Background The Australian Fire Danger Rating System program (AFDRS) has built a new fire danger rating system for Australia. A live trial of the system’s Research Prototype (AFDRSRP), based on fire behaviour thresholds, was run and evaluated between October 2017 and March 2018. Aims Live trial results are critically analysed, and knowledge gaps and recommendations for future work discussed. Methods Australian bushfire experts assessed wildfires and prescribed burns across a range of vegetation ty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

4
0

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 44 publications
0
11
0
Order By: Relevance
“…The AFDRS RP requires inputs of dynamic weather, fuel state and fire history as well as a fuel type grid that covers Australia. The outputs are a Fire Behaviour Index and a rating derived from the index indicating potential fire danger categorised into six levels (Grootemaat et al 2024;Hollis et al 2024). Index and category values were generated hourly, then summarised into daily and longer-term statistics, from January 2000 to February 2019.…”
Section: Methodsmentioning
confidence: 99%
“…The AFDRS RP requires inputs of dynamic weather, fuel state and fire history as well as a fuel type grid that covers Australia. The outputs are a Fire Behaviour Index and a rating derived from the index indicating potential fire danger categorised into six levels (Grootemaat et al 2024;Hollis et al 2024). Index and category values were generated hourly, then summarised into daily and longer-term statistics, from January 2000 to February 2019.…”
Section: Methodsmentioning
confidence: 99%
“…The AFDRS RP was found to accurately forecast fire danger 56% of the time compared with 43% by the McArthur system. The live trial highlighted a tendency for the AFDRS RP to overpredict rather than underpredict fire danger (Grootemaat et al 2024).…”
Section: Overview Of the Australian Fire Danger Rating Systemmentioning
confidence: 99%
“…During the southern fire season (October 2017-March 2018), a live trial evaluation of a Research Prototype version (AFDRS RP ) of the AFDRS was conducted to assess performance and reliability. The live trial demonstrated that a new national system was achievable and could provide clear community, economic and operational benefits (Grootemaat et al 2024). The AFDRS RP was subsequently endorsed by the Australian Government's MCPEM and moved to an implementation phase (Ministerial Council for Police and Emergency Management 2018) where additional practical components and local systems integration could be completed.…”
Section: Evolution Of the Australian Fire Danger Rating Projectmentioning
confidence: 99%
See 2 more Smart Citations